Natural Monomers Targeting the AMPK/GLP-1 Signaling Axis in the Treatment of Type 2 Diabetes: Molecular Mechanisms and Translational Prospects - Wang, Jiake; Wang, Yu; Yang, Ao; Niu, Yuqi; Wang, Songyi; Lei, Ye (Journal of Contemporary Medical Practice, 2026)
Type 2 diabetes mellitus (T2DM) is a progressive metabolic disease characterized by insulin resistance, beta-cell dysfunction, ectopic lipid accumulation, chronic low-grade inflammation, and multi-organ metabolic inflexibility. Although modern pharmacotherapy has greatly improved glycemic control, the durability of treatment responses remains constrained by disease heterogeneity, incomplete tissue coverage, adverse effects, and limited access in many settings. AMP-activated protein kinase (AMPK) and glucagon-like peptide-1 (GLP-1) signaling are two of the most validated metabolic axes in diabetes therapeutics. AMPK functions as a master energy sensor that suppresses hepatic gluconeogenesis, enhances skeletal muscle glucose uptake, promotes fatty acid oxidation, improves mitochondrial quality control, and dampens inflammation. GLP-1 regulates glucose-dependent insulin secretion, glucagon suppression, gastric emptying, appetite, and beta-cell survival, while also exerting extra-pancreatic actions in the liver, kidney, cardiovascular system, and central nervous system. Increasing evidence indicates that these pathways are not isolated. Instead, they intersect at the levels of intestinal L-cell biology, autophagy, mitochondrial homeostasis, inflammation, and tissue-specific insulin sensitivity, forming an integrated AMPK/GLP-1 signaling axis with substantial relevance to T2DM. Natural monomers have emerged as attractive modulators of this axis because they often act on multiple targets simultaneously, including intestinal nutrient sensing, DPP-4 activity, gut microbiota-derived incretin regulation, AMPK phosphorylation, oxidative stress, and inflammatory cascades. Representative compounds such as berberine, resveratrol, curcumin, quercetin, genistein, chlorogenic acid, epigallocatechin gallate (EGCG), naringenin, ginsenosides, and baicalin have shown anti-diabetic activity in cellular systems, animal models, and selected human studies. However, the literature remains fragmented, with many compounds being studied either as generic “anti-diabetic phytochemicals” or as isolated AMPK activators without sufficient attention to their mechanistic convergence with GLP-1 biology. This review synthesizes current evidence on the molecular crosstalk between AMPK and GLP-1 signaling and evaluates how natural monomers engage this axis across the gut-pancreas-liver-muscle-adipose network. We summarize representative compounds, compare their organ-level mechanisms, discuss pharmacokinetic and translational barriers, and outline priorities for future drug development. We argue that the AMPK/GLP-1 axis provides a useful conceptual framework for reclassifying natural monomers from single-pathway agents into network modulators with potential value as adjuncts, sensitizers, or leads for next-generation multi-target anti-diabetic therapies.